Opportunities offered by chiral η⁶-arene/N-arylsulfonyl-diamine-RuII catalysts in the asymmetric transfer hydrogenation of ketones and imines - Václavík, Jiří; Kačer, Petr; Kuzma, Marek; Cervený, Libor (Molecules, 2011)
Methods for the asymmetric transfer hydrogenation (ATH) of ketones and imines are still being intensively studied and developed. Of foremost interest is the use of Noyori's [RuCl(η⁶-arene)(N-TsDPEN)] complexes in the presence of a hydrogen donor (i-PrOH, formic acid). These complexes have found numerous practical applications and have been extensively modified. The resulting derivatives have been heterogenized, used in ATH in water or ionic liquids and even some attempts have been made to approach the properties of biocatalysts. Therefore, an appropriate modification of the catalyst that suits the specific requirements for the reaction conditions is very often readily available. The mechanism of the reaction has also been explored to a great extent. Model substrates, acetophenone (a ketone) and 6,7-dimethoxy-1-methyl-3,4-dihydroisoquinoline (an imine), are both reduced by this Ru catalytic system with almost perfect selectivity. However, in each case the major product is a different enantiomer (S- for an alcohol, R- for an amine when the S,S-catalyst is used), which demanded an in-depth mechanistic investigation. Full-scale molecular modelling of this system enabled us to visualize the plausible 3D structures of the transition states, allowing the proposition of a viable explanation of previous experimental findings.
Keywords: ketony; Hydrogenation; Molecular Structure; Stereoisomerism; Catalysis; molekulární struktura; hydrogenace; iminy; Imines; Ketones; katalýza; stereoizomerie